Maternal Mortality : Report June, 1932 (London : The Maternal Mortality Committee)
1932-06 1932 1930s 20 pages MATERNAL MORTALITY Chairman: Mrs. H.J. TENNANT, C.H., J.P. Hon. Secretary: MISS GERTRUDE M. TUCKWELL, C.H., J.P., 13 Chester Terrace, S.W.1. Hon. Treasurer; The COUNTESS OF IVEAGH, M.P. Committee: LADY BARRETT. M.D., C.H., Mrs. BARTON, J.P. [C.B.E., M.S. Mrs. BRAMWELL BOOTH, J.P. LADY MARGARET BOSCAWEN LADY CYNTHIA COLVILLE, J.P. LADY CROZIER The VISCOUNTESS ERLEIGH The VISCOUNTESS FITZALAN Miss ALICE GREGORY, O.B.E. Miss HALDANE, C.H., J.P. The DOWAGER VISCOUNTESS HARCOURT, G.B.E., J.P. Mrs. HUBBACK F. KERSHAW, Esq., O.B.E., J.P. Mrs. PIERCY, O.B.E. Mrs. USHER We have to chronicle with very deep regret the loss of a Member of our Committee, Dr. Marion Phillips, who died in January. Dr. Phillips brought to our work all the power of a great intelligence inspired by the deepest sympathy. Price .... 2/- per dozen, 12/6 per 100 292/824/1/58